Representation of japanese candlesticks by oriented fuzzy numbers - Krzysztof Piasecki; Anna yczkowska-Hanckowiak (Econometrics, 2020)
The Japanese candlesticks' technique is one of the well-known graphic methods of dynamic analysis of securities. If we apply Japanese candlesticks for the analysis of high-frequency financial data, then we need a numerical representation of any Japanese candlestick. Kacprzak et al. have proposed to represent Japanese candlesticks by ordered fuzzy numbers introduced by Kosinski and his cooperators. For some formal reasons, Kosinski's theory of ordered fuzzy numbers has been revised. The main goal of our paper is to propose a universal method of representation of Japanese candlesticks by revised ordered fuzzy numbers. The discussion also justifies the need for such revision of a numerical model of the Japanese candlesticks. There are considered the following main kinds of Japanese candlestick: White Candle (White Spinning), Black Candle (Black Spinning), Doji Star, Dragonfly Doji, Gravestone Doji, and Four Price Doji. For example, we apply numerical model of Japanese candlesticks for financial portfolio analysis.
Keywords: C02; C43; G19; 330; dynamic analysis of securities; Japanese candlestick; Kosinski’ s number; ordered fuzzy number; oriented fuzzy number